Assessment of reproductive ageing patterns by hormonal and ultrasonographic ovarian reserve tests - (:unkn) unknown (OXFORD UNIV PRESS, 2004)
Background: Tests to assess the change in ovarian reserve (OR) with age have been analysed only in monophasic or biphasic linear patterns. Our aim was to analyse an optimum curve that might define the relationship between different OR tests and age. Methods: A total of 81 regularly menstruating women without a history of infertility were included in this prospective study. On cycle day 3, antral follicle (AF) counts, ovarian volume (OV), and serum FSH and estradiol levels were determined. Curve estimation was performed to determine the optimal relationship between age and OR tests. Optimum curves were also compared with monophasic and biphasic linear relationships. Results: A quadratic model (y=axx(2)+bxx+c) had the highest coefficient of determination for the AF count, OV and serum FSH level. The predictive power of this quadratic model was comparable with biphasic linear models for the OV and serum FSH level, but was better than that of the AF count. Conclusions: The pattern of reproductive ageing as assessed by hormonal and ultrasonographic OR tests does not appear to show an abrupt change at a certain age, but follows a continuously increasing rate of decline in the third decade of life. The changes in serum FSH levels and ultrasonographic OR tests follow a quadratic model in regularly menstruating women.
Keywords: age; antral follicle; FSH; ovarian reserve; ovarian volume; TRANSVAGINAL SONOGRAPHY; FOLLICULAR DEPLETION; NATURAL FERTILITY; PROVEN FERTILITY; SCREENING METHOD; AGE; WOMEN; FOLLICLES; MENOPAUSE; DISAPPEARANCE